2019
DOI: 10.1186/s12985-019-1220-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum and tissue miRNAs: potential biomarkers for the diagnosis of cervical cancer

Abstract: Background Finding new biomarkers for the early detection of cervical cancer is an essential requirement in this field. In this study, we aimed to evaluate the expression level of potential biomarkers in progression of cervical cancer in patients with cervical cancer compared to normal subjects. Methods The expression levels of tissue and serum miRNAs, including miR-9, miR-192 and miR-205, were investigated in 36 normal, 18 precancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 60 publications
5
50
0
Order By: Relevance
“…miR-192-5p could functionally suppressed CSC features in HCC cells through targeting PABPC4 44 . Differently, the levels of serum miR-192-5p was significantly upregulated in nasopharyngeal carcinoma and cervical cancer 43,46 . This controversy indicate that miR-192-5p acts as either tumor-suppressive or oncogenic miRNA in different tumor types.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…miR-192-5p could functionally suppressed CSC features in HCC cells through targeting PABPC4 44 . Differently, the levels of serum miR-192-5p was significantly upregulated in nasopharyngeal carcinoma and cervical cancer 43,46 . This controversy indicate that miR-192-5p acts as either tumor-suppressive or oncogenic miRNA in different tumor types.…”
Section: Discussionmentioning
confidence: 85%
“…The genes which were also up-regulated in cervical adenocarcinoma tissues samples were shown. www.nature.com/scientificreports/ Aberrant expression of miR-192-5p has been reported in several tumors, such as hepatocellular carcinoma (HCC), non-small cell lung cancer (NSCLC), pancreatic cancer, and cervical cancer [42][43][44][45] . It was reported that miR-192-5p expression was significantly decreased in HCC, especially in cancer stem cell (CSC) + HCC.…”
Section: Discussionmentioning
confidence: 99%
“…After removing 158 duplicate articles, we included the eligible studies through reading titles and abstracts. Ultimately, ten articles [31,[47][48][49][50][51][52][53][54][55], covering 50 studies, were included according to the inclusion and exclusion criteria. Figure 1 showed the flow diagram of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Jia et al found that serum miRNA panel as the diagnostic fingerprint of CC had sensitivity, specificity, and AUC of 88.6%, 81%, and 0.908, respectively [48]. In addition, Farzanehpour et al showed that serum miR-192 can be a potential diagnostic biomarker for early detection of CC, with 83.3% sensitivity, 94.4% specificity, and 0.98 AUC [54]. Luo et al demonstrated that serum miR-3142 was significantly upregulated in CC patients, with the AUC of being 0.935 (95% CI: 0.893-0.977) [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation